Impact of climate change on solar and wind electricity generation in Aotearoa New Zealand - Lafargue, Clara; Brent, Alan (Archives of Sustainable Energy Systems, 2025)
Climate change is driving the energy sector with significant impacts on renewable electricity generation systems. The purpose of this study is to analyse the impact of climate change on solar and wind electricity generation in Aotearoa New Zealand projected to 2050. To have realistic and tangible results and reduce the uncertainties, climate change is modelled with three climate and economic scenarios. The annual electricity generation projected for 2050 is estimated through simulations conducted with SAM (System Advisor Model), using data provided by NIWA. The projected energy output in 2050 is compared with the electricity production of two solar farms and five wind farms in 2024. The results show that solar electricity generation will be similar to the data that the Electricity Authority captured for 2024, with some slight seasonal variations. Wind-generated electricity is likely to be more affectedby climate change, with a substantial increase in average wind speed in winter and spring, especially on the southern island. A decrease in wind in summer and autumn reduces wind-generated electricity. The risks to the reliability and stability of solar and wind power generation systems are particularly amplified by the increase in extreme weather events, such as intensified storms, atmospheric rivers, and floods. This study highlights the vulnerability of Aotearoa New Zealand’s energy sector to climate change, and the need for adaptation strategies. The recommendations include flexibility of power grid management with alternative sustainable electricity generation solutions and storage strategies and strengthening solar and wind farm infrastructure to make them more resilient and durable against extreme weather events.